CRIAÇÃO DE COPO PARA ALIMENTAÇÃO ORAL DE LACTENTES COMO ESTRATÉGIA DE PROMOÇÃO, PROTEÇÃO E APOIO AO ALEITAMENTO MATERNO - Stankiewicz, Andréia (2023)
To review scientific evidence on the feeding of newborns with breastfeeding difficulties through different models of cups and list the main characteristics that should be considered for the development of an efficient device; then create a cup for the oral feeding of infants to be used as an alternative method as a strategy to promote, protect and support breastfeeding. Methods: An integrative review of the literature was performed through a systematized search for relevant articles in the MEDLINE/PubMed, SciELO and Scopus databases. The descriptors and keywords were “infant, premature”, “infant, newborn”, “cup”, “cup feeding”, “feeding methods”, breastfeeding”, “feeding” and “infant feeding”, which were combined using the Boolean operators OR and/or AND. Data collection was performed between February and August 2022 and updated in April 2023. Articles that described the models of the devices being analyzed were included in the review. The devices, respective characteristics, advantages and disadvantages were analyzed to serve as the basis for the creation of an original product in partnership with the Projects in Design Lab of the Franciscan University in the city of Santa Maria, state of Rio Grande do Sul, Brazil, between July 2022 and March 2023. Design Thinking was the method used in the creation process of the feeding cup, using the following steps: (1) immersion: an exploratory documental research was conducted on the oral feeding process of infants by a cup, along with synchronic analysis for the identification of existing cups in the market and a survey of the needs of clients; (2) analysis and synthesis: the hierarchization of needs was determined using a Mudge diagram; (3) ideation: options were generated using the morphological matrix method, along with the conceptual project through the combination of the best options generated and, subsequently, the preliminary project was created for the definition of materials and measurements as well as the refinement of the drafts; (4) prototyping: this phase involved the development of the visual identity, the definitive project with the representation of the technical drawings and photorealistic images (renders, the submission of forms to register the protection of intellectual property and the physical modeling of the prototypes for the preliminary test and validation.Results: The searches of the databases led to the retrieval of 286 articles, 101 of which were duplicates and 124 did not meet the inclusion criteria. Sixty-one articles were submitted to full-text analysis and eight were selected to compose the final sample. Among the cup models, the paladai/palady (traditional device of Asian origin), the NIFTY® cup (trademarked model), the standard medicine cup and the disposable (coffee) cup were characterized. The need was identified for the cups to be ergonomic, easy to clean and anatomically compatible with the oral cavity of the newborn, enabling adequate functioning with physiological stability, adequate feeding time and minimal waste. Models developed specifically for the purposes of feeding seem to be better accepted by caregivers and healthcare providers, promoting more satisfactory experiences as an alternative to breastfeeding. However, no ideal cup model was found. The criteria for devices related to the infant, caregiver/provider, technique and product were listed and served as the basis to guide the fabrication of the product. The nature of the technical-technological product created is an intellectual property assess. Technical drawings were developed for a cup anatomically adequate for the mouth of infants in .pdf, .jpg and rendered images detailing the measurements and characteristics of the device, which has multiple functions: besides oral feeding, the device also serves as a recipient for the collection, transport and storage of human milk or formula. The “Mamacup” trademark was created, with the name and symbol submitted for the registration of intellectual property. The preliminary result of the product culminated in the generation of a three-dimensional prototype, giving form to the “Mamacup”, which is an intelligent solution for alternative feeding to be tested and validated in the future. Final considerations: The feeding of newborns through a cup constitutes a protection method for effective, safe breastfeeding supported by current scientific literature. However, few models were identified and none united all characteristics of ideal functioning. “Mamacup” was developed with functional, anatomical characteristics to protect breastfeeding, minimize the loss of milk and optmize adherence to the method. Product and applicability: “Mamacup” (intellectual property asset) is a promising multifunctional device that constitutes an intelligent option for oral feeding to assist the mother-infant dyad in dealing with contexts of challenging breastfeeding. The creation of a cup with intuitive use that is anatomical, functional, ergonomic, safe and scientifically based constitutes a promising tool in support to the clinical management of breastfeeding and is an important strategy in the promotion of public health through breastfeeding.